TEACHING SPELLING THROUGH GAMES - Hijjatul Qamariah; Sri Wahyuni (Jurnal Visipena, 2018)
Games have been believed to be good media in assisting teaching for years. Games are believed can promote learning become more interesting. Many studies have been conducted on utilizing games in learning. Some have proved that games can catch students’ attention better than traditional media such as textbook. In this study, games were used in teaching students about spelling. Since spelling is the basic form of language, there are still contradicts in how to teach it better. The researchers believed that games can assist in enacting more interactive spelling course well. Thus, this research employed some spelling games to be used in teaching third grade students of English as a Foreign Language (EFL) Elementary school, Bungcala, Aceh Besar. The researchers wanted to know the students’ responses after teaching by using spelling games. Thus at the end of teaching and learning process after four meetings by applying games in teaching spelling, the researcher distributed questioners to students asking their opinion about spelling games in learning spelling. The students’ responses showed that they love to study spelling through games, games make them interested in studying spelling. Games let them work more in groups.